The effect of the implementation active birth technique using hypnobirthing accelerated the progress of the first stage of labor among intrapartum mother - Darma, Ika Yulia; Abdillah, Nurul; Idaman, Meldafia; Morika, Honesty Diana (International Journal Of Community Medicine And Public Health, 2020)
Background: Problems in childbirth, including old labor, which is one of the causes of death for mothers and newborns, is still widely found in Indonesia. Factors that influence labor to take longer are abnormal presentation, inadequate contractions, birth canal abnormalities, multiple pregnancies and anemia. To deal with prolonged labor, the UK has introduced active birth techniques. Hypnobirthing is one of the active birth methods that can be used during the first stage of labor. This research purposes to study the effect of the application of the active birth technique using hypnobirthing on the progress of the first stage of labor in the mother. Methods: This type of research was quasi experimental with the post-test only design approach. This research was conducted from 15 May to 18 August 2020, in 4 independent practice midwives (BPM) Padang City in 2020. Data were collected through observation sheets using non-probability sampling techniques, namely purposive sampling with a total sample of 15 samples. Data were collected using observation sheets. Data were analysed using univariate and bivariate analysis using the dependent T-test. Results: The results showed that the mean labor progress using hypnobirthing was 3.67 and SD±1.49 with a minimum value of 1 and a maximum of 6. Based on the statistical test, the p value was 0.000 (p<0.05). Conclusions: There is the effect of the application of active birth techniques using hypnobirthing on the progress of stage I labor in maternal labor.